INVESTIGATING STUDENTS' LEARNING MOTIVATION IN PROJECT-BASED LEARNING - Barlian, Yelly Andrian (2015)
This thesis investigated how the project-based learning integrated with ARCS (Attention, Relevance, Confidence, and Satisfaction) motivational model was conducted in an art and design tertiary school, what categories of ARCS motivational model that affected the students most, including to find out what challenges they encountered. The aim of this study was to enhance English teaching material and strategies to develop and sustain student' learning motivation, particularly in writing activity. It is because motivation is considered one of crucial factors in learning process, especially in learning English as second language/foreign language. The participants involved are 38 students of visual communication design study program. A case study methodology was used in this research, and data were gained from several sources. The observation was conducted inside and outside classes to find out how the program was conducted for 14 meetings. They were recorded, described and interpreted; the questionnaire called Instructional Material Motivational Survey (IMMS) was delivered in the end of the program to investigate what motivational aspect that motivated the students most; the interview was given to the 12 students to confirm the observation result and notice the difficulties the students encountered in this project. Before the data were interpreted, they were recorder, transcribed and categorized into particular groups. The findings revealed that the students were highly motivated in the aspects of Attention, Relevance, and Satisfaction, and neutrally motivated in the aspect of Confidence. From the interview and the observation results it was found that it was due to the EFL learners' limited English language skill and the personal problems within teams, not to mention the overlapping tasks (Ates and Eryilmaz: 2010). However through this learning method the students were also experienced some beneficial impacts such as collaboration, communication skill, critical thinking's and other good learning attitudes. The results of this study were consistent with previous work performed by Boscolo and Gelati (2007), and Alhasan (2014). Referring to the research findings, it was inferred that apart from the teaching strategies and students' internal problems, the role of faculties and institution also has a very significant factor. Concerning this fact, integrating English with the other courses which are considered the major subject can be endeavoured to provide a great chance to collaborate among interdisciplinary teachers. An experimental research is recommended to confirm and determine the effects. Key words: Learning Motivation, ARCS Model, Project-Based Writing Activity